2017
DOI: 10.1002/1878-0261.12137
|View full text |Cite
|
Sign up to set email alerts
|

An individualized gene expression signature for prediction of lung adenocarcinoma metastases

Abstract: Our laboratory previously reported an individual‐level signature consisting of nine gene pairs, named 9‐GPS. This signature was developed by training on microarray expression data and validated using three independent integrated microarray data sets, with samples of stage I non‐small‐cell lung cancer after complete surgical resection. In this study, we first validated the cross‐platform robustness of 9‐GPS by demonstrating that 9‐GPS could significantly stratify the overall survival of 213 stage I lung adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…A four‐gene prognostic signature, including one lncRNA gene, has been previously reported for LUAD patients, which performs well in stage I patients as well as EGFR‐mutant and wild‐type cohorts . Similarly, other studies have focused on characterizing gene signatures for prognosis of lung cancers . Until now, only a few lncRNA signatures have been characterized and proposed as biomarkers for lung cancer prognosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A four‐gene prognostic signature, including one lncRNA gene, has been previously reported for LUAD patients, which performs well in stage I patients as well as EGFR‐mutant and wild‐type cohorts . Similarly, other studies have focused on characterizing gene signatures for prognosis of lung cancers . Until now, only a few lncRNA signatures have been characterized and proposed as biomarkers for lung cancer prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…9 Similarly, other studies have focused on characterizing gene signatures for prognosis of lung cancers. [22][23][24] Until now, only a few lncRNA signatures have been characterized and proposed as biomarkers for lung cancer prognosis. [25][26][27] In the current study, 735 lncRNAs were found differentially expressed between LUAD patients with and without metastasis, among which 43 lncRNAs were identified to be significantly associated with RFS of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous study, 34 the qualitative REOs‐based prognostic signature is highly robust against experimental batch effects and differences in probe designs of different platforms. Besides, the signature can be readily applied at an individualized level without data normalization, which is more reliable and practical than quantitative signatures for risk prediction 54 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, the signature can be readily applied at an individualized level without data normalization, which is more reliable and practical than quantitative signatures for risk prediction. 54 At present, most of the clinical tissue samples are fixed in FFPE blocks, [55][56][57] and stored in hospitals and tissue banks, which is a huge and precious resource for clinical research. 58 Nevertheless, FFPE samples are generally considered unreliable for gene expression analysis because of RNA degradation during preparation and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the qualitative signatures can be applied at the individual level [33]. Based on the within-sample relative expression orderings (REOs) of gene pairs, we have developed prognostic signatures for many cancer types [28,[34][35][36] and demonstrated their robustness in both interlaboratories and across-platforms tests [29,37].…”
Section: Introductionmentioning
confidence: 99%